Certyfikaty i nagrody jako formy upowszechniania koncepcji społecznej odpowiedzialności organizacji - Rogala, Piotr (Annales. Etyka w Życiu Gospodarczym, 2008)
The interest of the contemporary companies is not only in the fulfillment of social responsibility rules but also in the ways to reliably inform the community about their ‘ethical face’. Such possibility is created by, functioning in economy, systems of awarding certificates, distinctions, prizes etc. (e.g. Przejrzysta Polska, SA 8000, Filary Polskiej Gospodarki, Gender Index, Firma Fair Play etc.). The article characterizes and performs a comparative analysis of the most important initiatives of this kind in Poland.